SUPPORTING FACTORS IN ENGLISH LEARNING PROCESS OF CHILDREN - Poetryku Syahara Noh (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
Becoming widely usage foreign language, English become very important to learn and it needs to be learnt many people since child to old people based on their needs. In formal or non-formal study, people learn English. Learning English needs some process to get success learning. The process for the young learners or old learners are different. Some can learn quickly some spend more time. Sometimes children learn more quickly than old learners, sometimes old learners learn more quickly. It has some supporting factors in English learning process. Children are young learners who need process in learning foreign language; English. Some factors support the process of learning English are environment, motivation, learning methods, aptitude, intelligence and ability to learn. To get succeed in learning language those must be balanced and support one another. After knowing those factors, learners or teacher can manage the factors based on each condition and abilities in order to get the foreign language well. Helping in deciding the teaching method, learning method, media, etc.